The effect of a polyacrylic acid viscosity modifying agent on the mechanical, thermal and transport properties of hemp and rapeseed straw concrete. (28th February 2020) - Sheridan, Joseph; Sonebi, Mohammed; Taylor, Su; Amziane, Sofiane
Highlights: The effect of weathering is studied on vegetal concretes with and without a VMA. Both hemp and rapeseed concretes were susceptible to long term weathering. VMA usage increases the resistance of hemp and rapeseed concretes to weathering. Outdoor weathering had no effect on the compressive strength of all mix types. In all mixes, binder and organic compounds were found to have leached over time. Abstract: In recent decades sustainability, carbon footprint and pollution have become significant issues on a global scale. It is widely recognised that the carbon footprint of the construction industry can be reduced which has led to sustainable materials being used more and more widely to meet emissions targets. Two of these materials are hemp concrete and rapeseed-straw concrete which are bio-composites made of a bio-aggregate, water and a lime binder, in this investigation Vicat prompt natural cement (PNC). The addition of a viscosity modifying agent (VMA) is studied for its effect on the mechanical, thermal and transport properties. It was found that the use of a VMA was very effective at countering the two biggest weaknesses of bio-based building materials as it reduced the capillarity absorption of the concrete significantly and also greatly increased the compressive strength and modulus of elasticity of the material.